'Losing Leverage' in the Neighbourhood: A Cognitive Frame Analysis of the European Union Migration Policy. (July 2021) - Jäntti, Jyri J.; Klasche, Benjamin
The European Union (EU)–Turkey deal consolidated a shift in the EU's migration policy. The deal is the culmination of the dominance of the security frame and depicts the continuous externalization of the EU's responsibility of asylum protection and burden sharing. The strengthening of the security frame has weakened the humanitarian norms that previously dictated EU's behaviour. This has led to the EU losing some of its comparative advantages in negotiations. Simultaneously, the instrumentalization of the value of asylum, paired with an increased number of asylum seekers, has given negotiation leverage to the neighbouring countries turned service providers. These changes in perception and norms have created a power shift, at the disadvantage of the EU, creating a more leveled playing field for negotiations between the parties. This article tracks the historical shifts in the global refugee regime to explain how today's situation was created. Hereby, the existence of two competing cognitive frames—humanitarian and security—is assumed, tracked and analysed. While looking at the EU–Turkey deal, the article shows that the EU has started treating refugees as a security problem rather than a humanitarian issue, breaking the normative fabric of the refugee regime in the process. The article also displays how Turkey was able to capitalise on this new reality and engage with negotiations of other neighbouring countries of EU that point towards a change of dynamics in the global refugee regime.